Analsis Uji Sifat Fisis dan Mekanis Tanah Clay Shale Yang Distabilisasi Dengan Penambahan Kapur dan Fly Ash - Fuad Harwadi; Hasrullah Hasrullah; Dana Febriansyah (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2025)
Clay shale soils have properties that are very easily weathered or weakened in a relatively short time when reacting with air and water. Therefore, it needs to be stabilized to improve its technical properties and bearing capacity. This study aims to determine the optimal percentage of fly ash and lime addition as stabilizer materials. The addition of stabilizer to soil samples was carried out by varying the percentage of addition of 15%, 20% and 25% with variations in the length of curing time for 14, 21 and 28 days. Furthermore, physical and mechanical properties were tested in the form of CBR and UCT tests. The test results showed a change in soil grain size where there was an increase in sand content and a decrease in clay content in all samples. This occurs due to the pozzolanic process. The addition of stabilizer also affects the increase in CBR and UCT test values, where the most optimal increase occurs in the addition of 15% stabilizer with 28 day curing period. The CBR value increased by 110% while the UCT value was 38.25 kg/cm2 from the initial condition